Sources and variability of CO2 in a prealpine stream gravel bar. Issue 17 (24th June 2019) - Boodoo, Kyle S.; Schelker, Jakob; Trauth, Nico; Battin, Tom J.; Schmidt, Christian
Abstract: Gravel bars (GBs) contribute to carbon dioxide (CO2 ) emissions from stream corridors, with CO2 concentrations and emissions dependent on prevailing hydraulic, biochemical, and physicochemical conditions. We investigated CO2 concentrations and fluxes across a GB in a prealpine stream over three different discharge‐temperature conditions. By combining field data with a reactive transport groundwater model, we were able to differentiate the most relevant hydrological and biogeochemical processes contributing to CO2 dynamics. GB CO2 concentrations showed significant spatial and temporal variability and were highest under the lowest flow and highest temperature conditions. Further, observed GB surface CO2 evasion fluxes, measured CO2 concentrations, and modelled aerobic respiration were highest at the tail of the GB over all conditions. Modelled CO2 transport via streamwater downwelling contributed the largest fraction of the measured GB CO2 concentrations (31% to 48%). This contribution increased its relative share at higher discharges as a result of a decrease in other sources. Also, it decreased from the GB head to tail across all discharge‐temperature conditions. Aerobic respiration accounted for 17% to 36% of measured surface CO2 concentrations. Zoobenthic respiration was estimated to contribute between 4% and 8%, and direct groundwater CO2 inputs 1% to 23%. Unexplained residuals accounted for 6% to 37% of the observed CO2 concentrations at the GB surface. Overall, we highlight the dynamic role of subsurface aerobic respiration as a driver of spatial and temporal variability of CO2 concentrations and evasion fluxes from a GB. As hydrological regimes in prealpine streams are predicted to change following climatic change, we propose that warming temperatures combined with extended periods of low flow will lead to increased CO2 release via enhanced aerobic respiration in newly exposed GBs in prealpine stream corridors.